Effects of postactivation performance enhancement on the vertical jump in high-level volleyball athletes - Berriel, G. P.; Cardoso, A. S.; Costa, R. R.; Rosa, R. G.; Oliveira, H. B.; Kruel, L. F. M.; Peyré-Tartaruga, L. A. (Journal of Human Kinetics, 2022)
The objective of this study was to evaluate the effects of a training session with and without an intervention of postactivation performance enhancement (PAPE) on countermovement jump (CMJ) height, perceived recovery status (PRS), and ratings of perceived exertion (RPEs), followed by a specific volleyball training session. The sample consisted of sixteen professional male volleyball players, with an average age of 26.8±6.1 years and average height of 195.9±6.7 cm, randomly divided into a group with PAPE intervention (GPAPE) (n=8), and a control group (CTRL) without PAPE intervention (n=8). The control group carried out the training session with plyometric exercises, and the GPAPE added conditioning protocols for PAPE to plyometric training, followed by a technical tactical volleyball session. At the end of the training session, there was an increase of 16.3% in the height of the CMJ in the GPAPE, while the CTRL showed a decrease of 5% in the height of the CMJ. PRS and RPE variables did not differ between the groups. It was concluded that PAPE had a positive effect on the height of the vertical jump after plyometric training, which was maintained until the end of the technical and tactical volleyball session.